A method for praecordial surface mapping of the exercise electrocardiogram. Issue 12 (December 1978) - Fox, K M; Selwyn, A P; Shillingford, J P
Abstract : A technique for praecordial surface mapping of the exercise electrocardiogram is described. This showed the area, time course, and severity of ST segment depression as projected onto the front of the chest after exercise. Twenty normal volunteers and 20 patients with coronary artery disease have been studied. No changes were seen after exercise in the normal subjects but areas of ST segment depression appeared in all 20 patients with angina pectoris. In 5 of the 20 patients with coronary artery disease, the exercise test was repeated on a later date. There were no significant differences in the area of severity of electrocardiographic abnormalities recorded during the two tests. This technique may prove to be useful for diagnosis and assessing medical and surgical treatments in patients with ischaemic heart disease.